The impact of methylene blue photosensitizer, aPDT and a calcium hydroxide-based paste on the physicochemical and mechanical characteristics of root canal dentin and the bonding interface of fiberglass posts - Strazzi-Sahyon, Henrico Badaoui [UNESP]; Banci, Henrique Augusto [UNESP]; Maltarollo, Thalya Fernanda Horsth [UNESP]; Martinez, Carolina Martins Teixeira [UNESP]; Rocha, Eloísa Alexo; Figueiredo, Roberto Braga; Garcia, Dayana Cristina Silva; Constantino, Carlos José Leopoldo [UNESP]; Spin-Neto, Rubens; Duarte, Marco Antonio Hungaro; Cintra, Luciano Tavares Angelo [UNESP]; Santos, Paulo Henrique dos [UNESP]; et al. (Elsevier, 2024)
Purpose: To investigate the influence of methylene blue (MB)-mediated antimicrobial photodynamic therapy (aPDT) and calcium hydroxide (CH) medication on the mechanical characteristics, degree of conversion (DC), quantification, and volume of gaps at the adhesive interface of glass fiber posts (GFPs) luted to distinct thirds of root canal dentin. Additionally, the microhardness (MH), elastic modulus (Eit), morphology, and chemical structure of the intraradicular dentin were assessed. Materials and methods: 6 experimental groups were formed by sorting 102 bovine incisors. Canals receiving deionized water irrigation as a negative control; canals receiving deionized water irrigation and filled with CH as a positive control; groups treated with CH + MB at 50 and 100 mg/L without irradiation; and groups treated with CH + MB at 50 and 100 mg/L irradiated by red laser for 60 s (660 nm; 100 mW; 6.5 J; 72 J/cm2). MH, Eit, and DC properties were evaluated for both the resin cement layer and root dentin substrate (n = 8). Volume and quantification of gaps at the bonding interface (n = 6), and dentin morphology and chemical content were investigated (n = 3). Data were analyzed using a repeated-measures 2-way ANOVA followed by Tukey post hoc analysis (α = 0.05). Results: The distinct intraradicular thirds and treatment with MB-mediated aPDT, whether activated or not, in combination with CH, had a significant impact on the mechanical characteristics of the root dentin. This effect was also observed in the MH, Eit, DC, quantification, and volume of gaps at the luting interface (P < .05). In general, a higher concentration of MB, whether activated by a red laser or not, led to lower values in the mechanical properties of the root dentin, as well as in MH, Eit, and DC at the adhesive interface (P < .05). Additionally, these groups exhibited higher values for quantification and volume of gaps at the luting substrate (P < .05). Scanning electron micrographs and energy dispersive X-ray spectra showed qualitative similarity among all groups, except for the negative experimental control group. Conclusions: MB-mediated aPDT at 50 mg/L, in combination with CH, demonstrated favorable physico-chemical and mechanical characteristics in intraradicular dentin, along with satisfactory mechanical features and the adhesive interface integrity for GFPs at all intraradicular depths. Clinical significance: MB-mediated aPDT at a concentration of 50 mg/L combined to CH medication represents a suitable choice for photosensitization in the context of intracanal disinfection following the biomechanical procedure and prior to luting of intraradicular restorations.
Keywords: Calcium hydroxide; Degree of conversion; Dentin; Mechanical properties; Methylene blue; Photodynamic therapy